1995
DOI: 10.2535/ofaj1936.72.2-3_137
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Taste Buds on the Epiglottis of the Rat and House Shrew, with Special Reference to Air and Food Pathways

Abstract: We investigated the positioning of the epiglottis in the pharyngo-laryngeal region and the distribution of taste buds on the epiglottis in the rat and house shrew, animals which have different feeding habits. In the fixed samples of both species, when the mouth was closed or slightly opened, the epiglottis was found to protrude into the nasopharyngeal hiatus above the soft palate. But it retracted from its position when the mouth was widely opened. In omnivorous rats (n = 6), the mean number (mean density +/- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Shrestha et al. () demonstrated that only a few ‘taste buds’ were distributed near the edge of the oral surface of the epiglottis. In contrast, in the present study, chemosensory cell clusters were concentrated at the anterior border of the larynx, including the edge of the epiglottis, aryepiglottic fold, and mucosa covering arytenoid cartilage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Shrestha et al. () demonstrated that only a few ‘taste buds’ were distributed near the edge of the oral surface of the epiglottis. In contrast, in the present study, chemosensory cell clusters were concentrated at the anterior border of the larynx, including the edge of the epiglottis, aryepiglottic fold, and mucosa covering arytenoid cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…The mucosa overlying epiglottic cartilage may also be a receptive field for chemical stimuli. Chemosensory cell clusters have been reported as laryngeal taste buds in various species (Travers & Nicklas, 1990;Sweazey et al 1994;Shrestha et al 1995;Nishijima & Atoji, 2004;Sbarbati et al 2004b). Chemosensory clusters are mainly distributed in the laryngeal surface of the epiglottis and aryepiglottic fold in the rat larynx (Nishijima & Atoji, 2004;Sbarbati et al 2004b).…”
Section: Distribution Of Chemosensory Cells In the Laryngeal Mucosamentioning
confidence: 99%
See 1 more Smart Citation
“…Sherestha et al. 6 suggested that because the number of epiglottal taste buds varies by species, their presence may correlate with feeding habits. It could be suggested that in elderly people, the decrease of epiglottal taste bud density on the laryngeal surface may have an effect on the reflex response during swallowing.…”
Section: Discussionmentioning
confidence: 99%
“…The hamster epiglottis is said to contain about 10% of the total number of taste buds 4 , whilst the human epiglottis is estimated to contain up to 25% of the total. Although taste buds are sensory organs, those on the epiglottis may have an important role in protecting the upper airway by functioning as chemical receptors 5,6 However, age‐related changes on the number and distribution of epiglottal taste buds have not been fully investigated and whether they continue to play a functional role in protecting the upper airway. Previous studies have documented age‐related changes in the number of taste buds in the epiglottis of the rat 7 and sheep 8 .…”
Section: Introductionmentioning
confidence: 99%